Validity of the EQ‐5D in pemphigus. (1st April 2019) - Tamási, B.; Brodszky, V.; Péntek, M.; Gulácsi, L.; Hajdu, K.; Sárdy, M.; Szegedi, A.; Bata‐Csörgő, Z.; Kinyó, Á.; Rencz, F.
Summary: Pemphigus is a group of autoimmune skin diseases that cause blisters and wounds on the skin and/or mucous membranes such as inside the mouth. It is an uncommon disease with around 15 new cases yearly per million people. The two most common clinical forms are pemphigus vulgaris and foliaceus. Pemphigus can still be life threatening, and the symptoms may cause significant difficulties for patients in their everyday life. This study, from Hungary, aimed to assess the health status and quality of life in patients with pemphigus vulgaris and foliaceus. The authors surveyed 109 pemphigus patients, and collected data on demographics and clinical characteristics. Quality of life was assessed by the EQ‐5D general health status questionnaire. Overall, 50%, 43%, 43%, 42% and 19% of pemphigus patients reported problems regarding pain/discomfort, mobility, anxiety/depression, usual activities and self‐care, respectively. Patients having skin and mucosal symptoms, a larger number of comorbidities (other diseases occurring alongside pemphigus) and more severe disease experienced greater impairment of quality of life. No difference was found in quality of life scores between pemphigus vulgaris and foliaceus patients or between females and males. This study demonstrates that the EQ‐5D questionnaire is an accurate measure of quality of life in pemphigus patients. The EQ‐5D questionnaire allows comparisons between patients across a broad range of disease areas and people without those diseases. The EQ‐5D scores reported in this study can be useful for cost‐effectiveness analyses of new pemphigus treatments such as rituximab, and might help to improve patients' access to more effective medicines, in a condition for which only limited treatment options have been available so far.